Perbedaan Pengetahuan Ibu Primipara dan Multipara tentang Cara Menyusui yang Benar pada Bayi Umur ( 0–6 Bulan ) di BPM Siswati, A.Md Keb Desa Sumbersuko Kec. Curahdami Kab. Bondowoso - dewi rakhmawati (Universitas Islam Jember, 2018)
Abstract The low level of exclusive breastfeeding among women giving birth in Indonesia is caused by several factors, one of which is the low knowledge of mothers about the benefits of breastfeeding for mothers and babies. Other reason is a lack of care and support from husbands, families and communities to provide opportunities for mothers to breastfeed exclusively. Impact of low knowledge of mother about how to breastfeeding correctly are usually can arise odema of mammae, nipple blisters, breast inflammation, lack of milk, confused baby nipples (due to the use of pacifier or kempeng). This study aims to determine the differences in knowledge of primipara and multiparous mothers about how to breastfeed correctly for infants aged 0-6 months. This research is observational analytic. The design of this research used a cross sectional approach. The population in this research were all breastfeeding mothers who had a baby age (0-6) in either primipara or multipara which was 40 people. The sampling technique in this research was total sampling (Non Probability Sampling). Based on differences in knowledge of primipara and multiparous mothers, it can be interpreted that almost all respondents were well-informed, especially in multiparous mothers, namely 14 (77.7%). Where as in the correct way of breastfeeding is found in multiparous mothers. The results of statistical tests obtained a value of P = 0.005 <a = 0.05, it can be concluded that there is a difference in knowledge of Primipara and Multipara (X1) mothers about how to breastfeed correctly in infants aged (0-6) months (X2). Keywords: knowledge of primiparous and multiparous mothers, the correct way of breastfeeding